Peningkatan Kreativitas Belajar Siswa Kelas III pada Materi Seni Rupa melalui Teknik Kolase - Andani Rahmawati, Sajidda; Amelia Sani, Fidela; Ermawati, Diana (STKIP PGRI Ponorogo Press, 2024)
This research aims to improve students' creative learning abilities using collage techniques. The research method used was classroom action research (PTK) using quantitative and qualitative approaches. The research subjects were 20 class III students at SD 03 Wergu Wetan. This research took place over 2 cycles consisting of 2 meetings in each cycle with planning, implementation, observation and reflection phases. The instruments used in this research include observation sheets and interview guidelines. Data collection techniques use observation, interviews and documentation. The research results showed that from cycle 1 to cycle 2 there was an increase of 20% to 50% in the sufficient category. Thus increasing the learning creativity of class III students through collage techniques can be said to be successful.